Estudio de prefactibilidad para la instalación de un bar de hielo temático en Cusco - Goñi Harrisson, Christian (2019)
The purpose of this work is to determine if it is convenient to install a thematic ice bar in the city of Cusco. To achieve this end, factors from different origins will be analyzed. The research plan will include the methodology to be applied in the work, the objectives, the references, the schedule of activities, the glossary of terms and the definition of the service. Since, in this case, it is about the investigation of a service, a flow chart will be used as well. With the research plan completed, a market study will begin. This study will determine the pre-feasibility of the project from the point of view of demand. Then, a study for the location of the service and another for the size of the service establishment will be carried out. Finally, a cost analysis and a financial one will determine if the project is convenient from the economic point of view. The financial analysis will take a 6-year projection and a suitable interest rate for the market.